Data Traffic Analysis on an Electric Current Monitoring System - Romadhon, Mohammad Rizki; Arrofiq, Muhammad (Department of Electrical Engineering and Informatics, Vocational College, Universitas Gadjah Mada, 2020)
Change and Innovation continues as the times progress. Especially in the field of technology, one of which is the Internet of Things (IoT). With the existence of this technology, electronic devices can be connected to the internet. This will simplify the process of data transmission and device control. With this aim, the authors do research on the implementation of IoT technology on electronic devices, especially in the field of electricity. Electrical energy monitoring systems are used to detect the use of electrical energy used by the load. In this monitoring system, the measurement of the electric current using the current sensor. The measurement data made by the current sensor will be processed by the microcontroller. The research developed arduino-based monitoring systems and databases aimed at detecting and monitoring the use of electric current. In addition, it also performs analysis of data traffic from arduino devices and databases, to find out data delay, throughput or packet loss by using Wireshark.